THE INFLUENCE OF PRODUCT QUALITY AND SERVICE QUALITY ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AT BANK SYARIAH INDONESIA KCP PANDAAN PASURUAN - Qudratullah, Muhammad Qori; Firmansyah, Fani (JURNAL DIMENSI, 2024)
The purpose of this study is to analyze and explain the effect of product quality and service quality on customer loyalty with customer satisfaction as an intervening variable at PT Bank Syariah Indonesia Pandaan Pasuruan Sub-Branch Office. This research method uses quantitative research and descriptive statistical analysis. The sampling technique in this study used convenience samples. The sample in this study amounted to 145 respondents who came from customers of Bank Syariah Indonesia KCP Pandaan Pasuruan. Data collection using questionnaire distribution techniques, research disseminating a list of questions to customers who use products at PT Bank Syariah Indonesia Pandaan Pasuruan Branch Office. The results showed that product quality had a significant effect on customer loyalty but service quality did not have a significant effect on customer loyalty at Indonesian Islamic banks at KCP Pandaan. Product quality does not have a significant effect on customer satisfaction but service quality has a significant effect on customer satisfaction at Indonesian Islamic banks at KCP Pandaan. Customer satisfaction has a significant effect on customer loyalty to Indonesian sharia banks at KCP Pandaan. Customer satisfaction is not able to mediate the effect of product quality on customer loyalty at Indonesian sharia banks at KCP Pandaan, but customer satisfaction is able to mediate the effect of service quality on customer loyalty at Indonesian sharia banks at KCP Pandaan.